Development of Traditional Hopscotch Game Learning Media Based on Ethnomathematics in Class IV 9 Sila State Elementary School - Sarafiah, Siti; Khatimah, Husnul (Noumerico: Journal of Technology in Mathematics Education, 2023)
Mathematics is a basic subject that is taught from an early age, including two-dimensional material. The process of that material in mathematics tends to be developed through conventional teaching patterns. This makes the two-dimensional material canâ€™t to be understood well by students and has an impact on students' low math scores. It is necessary to develop learning media in this study in the form of learning media for traditional hopscotch games based on ethnomathematics on two-dimensional geometric materials. This research is an R&D research with 4D type consisting of Define, Design, Development, and Disseminate. The instruments in this study were interviews, questionnaires, and documentation. Interviews were used to analyze teacher needs, questionnaires were used in product validation by validators, asking for student responses on small and large scale tests, and assessing teacher and student activity in learning and documentation to perpetuate research. It was found that the assessment criteria for all validators obtained very good scores with details of the learning media validator having an average score of 90.97% (very valid), the learning material validator having an average score of 99.10% (very valid), the learning problem validator has an average score of 99.16% (very valid). The small-scale test with 10 students has a classical percentage of 90.1% (very good). Meanwhile, a large-scale test with a total of 20 students obtained teacher activity having a score range of 98.68% (very valid), student activity having a score range of 90.90% (very good), student responses having an average score of 94.1% (Very good). While the results of the final evaluation of students using the two-dimensional hopscotch media obtained an average value of 83.85, the classical completeness score was 90% of the 18 students who scored â‰¥ 70. Thus the two-dimensional hopscotch media is feasible and very effective to use.